The effect of warm compresses on pain intensity in active phase 1 labor at the blue bone health center - Muldaniyah, Muldaniyah; Ani, Ani; Asli, Kartika (CV. Paperhome Indonesia, 2024)
Pain during labor is the pain that is felt in laboring mothers due to uterine contractions which is a physiological process of the human body when facing labor. Giving interventions in the labor process to reduce maternal pain that takes place during the first stage of the active phase of labor is needed, a very effective method in dealing with pain is to provide Warm compress action. The purpose of this study was to determine the effect of Warm compress e on the intensity of pain in pregnant women during the first active phase at the biru bone Public Health Center This type of research uses quantitative research with a quasi-experimental research design. The research design is one group pretest and posttest design. The sampling technique used is purposive sampling. The number of samples is 30 respondents. The analysis in this study used the Mc Nemarc test statistical test with a significance level of 95% (α 0.05). The results obtained before the warm compress was 26,7% who experienced mild pain, after being given warm compress there was an increase of 83,3% who experienced mild pain. Based on the Mc Nemarc test, the value of = 0.000 < 0.05, then Ha is accepted and Ho is rejected. Which means that there is an effect of warm compress on decreasing pain intensity in maternity mothers during the first active phase. Conclusion of this researchnamely warm compress is effective for reducing the intensity of pain in the first stage of the active phase in maternity because it's so focused at the point of pain, Thenexpected midwifein providing caremidwifery can apply warm compress to reduce pain intensity in maternity mothers.